Identifying the challenges of policy content related to high-risk sexual behaviors, stimulant drugs, and alcohol consumption in adolescents - Saeid Mirzaei; Mohammad Hossein Mehrolhassani; Vahid Yazdi-Feyzabadi; Abbas Jahanara; Ali Akbar Haghdoost; Nadia Oroomiei (BMC, 2024)
Abstract Background This study aims to identify policy content challenges related to high-risk sexual behaviors, stimulant drugs, and alcohol consumption in Iranian adolescents. Methods This qualitative study analyzed high-level and national documents pertaining to adolescent health, high-risk sexual behaviors, stimulant, and alcohol consumption in adolescents. The documents, which were published by public organizations between January 1979 and February 2023 and publicly available, were complemented by interviews with policymakers and executives. The study involved reviewing 51 papers and conducting interviews with 49 policymakers and executives at the national, provincial, and local levels who were involved in addressing adolescent behaviors related to high-risk sexual behaviors, stimulant, and alcohol consumption. The data collected was analyzed using conventional content analysis. Results The study's results involved examining policy content and identifying challenges related to policy content. The analysis revealed that from the beginning of the Iranian revolution in 1979 until the late 1990s, the dominant approach in Iran was to deny the existence of high-risk behaviors among adolescents. However, in the early 2000s, the country began to adopt a new approach that acknowledged the social harms and ineffectiveness of previous strategies. As a result, a new policy framework was introduced to address high-risk behaviors among adolescents. The study's interviews with policymakers and executives identified 12 challenges related to policy content, including parallel programs, lack of institutional mapping, lack of evidence-based policymaking, lack of integrated approach regarding training, late parent training, lack of consideration of all occurrence reasons in adolescents' high-risk behaviors policymaking, and the existence of many abstinence policies regarding high-risk behaviors. Conclusions The study's findings suggest that high-risk behaviors among adolescents in Iran are primarily a health issue, rather than a social or ideological one. Unfortunately, ideological approaches, stigma, and policymaking based on anecdotes rather than evidence have had a significant impact on this area. To improve policymaking in this domain, it is crucial to address these challenges by tackling stigma, adopting an integrated and holistic approach, and implementing evidence-based policies that consider all relevant aspects, including adolescents' subcultures and policy audiences. Such an approach can also be useful for other countries facing similar conditions.